Studi Tinjauan Sistematis: Hubungan antara Kelincahan Organisasional dan Kinerja UMKM - Maulidan, Rahmat; Gunanjar, Imam; Verinanda, Muhammad Ridwan; Syahputra, Rico; Hardianti, Anisha (Jurnal EMT KITA, 2025)
This study analyzes the relationship between organizational agility and the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia using a Systematic Literature Review (SLR) approach. The main focus of this review lies in the challenges faced by MSMEs in responding to an increasingly complex business environment. The study is conducted at the national level, with a particular emphasis on the dynamics of the MSME sector in Indonesia. A total of 50 scholarly articles were collected using the Publish or Perish software from prominent databases such as Scopus, Emerald Insight, DOAJ, Google Scholar, and SINTA. The analysis process involved several stages, including literature identification, screening based on inclusion criteria, data coding, and reporting of findings. The results indicate that organizational agility is a critical factor in enhancing MSME performance, particularly in terms of process efficiency, innovation, and resilience during times of crisis. Furthermore, agility also serves as a driver for digital transformation and improved business competitiveness. However, research gaps remain, especially in the context of the informal sector, rural areas, and the lack of longitudinal studies. These findings contribute to the theoretical discourse on organizational agility within MSMEs and offer practical recommendations for strengthening their adaptive capacity in the face of a rapidly changing business environmen.
Keywords: MSMEs; Organizational Agility; Digital Transformation; Performance; Systematic Literature Review (SLR); Innovation